FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA PETANI PADI DI DESA PRAJEGAN KECAMATAN SUKOREJO KABUPATEN PONOROGO - Ulfa, Elok Fadila; Darundiati, Yusniar Hanani; Setiani, Onny; Dewanti, Nikie Astorina Yunita (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2024)
The application of pesticides in agriculture can have an impact in environmental quality and cause health problems for farmers. Prajegan Village is one of the villages that uses a large amount of pesticides and the highest cases of hypertension in Sukorejo District. The aimed of this study was to find out the factors related to the incidence of hypertension among paddy farmers in Prajegan Village, Sukorejo District, Ponorogo Regency. This type of study was analytic observational with a cross-sectional design. The total population in the research was 718 paddy farmers. The sample in this study was 97 paddy farmers who was taken by purposive sampling. The data were collected using a questionnaire and sphygmomanometer. The results showed that as many 58 farmers (59.8%) had hypertension, low education level was found in 67 farmers (69.1%), working period >5 years was found in 81 farmers (83.5%), inappropriate pesticide doses were found in 57 farmers (58.8%), risky spraying time was found in 13 farmers (13.4%), the average spraying frequency of 1x/week was found in 66 farmers (68%), and the use of PPE <5 was found in 57 farmers (58.8%). Chi-square test results showed that there is correlation between education level (p= 0.047), working period (p= 0.023), pesticide doses (p = 0.002), the use of PPE (p= 0.023), and there is no correlation between spraying time (p= 0.439) and spraying frequency (p= 1.000). From this study, it can be concluded that the factors related to the incidence of hypertension are education level, working period, pesticide doses, and the use of PPE.